2005
DOI: 10.1161/circulationaha.104.531657
|View full text |Cite
|
Sign up to set email alerts
|

Vascular Smooth Muscle Overexpression of G Protein–Coupled Receptor Kinase 5 Elevates Blood Pressure, Which Segregates With Sex and Is Dependent on G i -Mediated Signaling

Abstract: Background-Essential hypertension involves an increase in sympathetic nervous system activity and an associated decrease in ␤-adrenergic receptor (AR)-mediated dilation. In addition, increased levels of G protein-coupled receptor (GPCR) kinases (GRKs), which regulate GPCR signaling, are associated with increased blood pressure (BP). Methods and Results-We generated transgenic mice with Ϸ2-fold vascular smooth muscle (VSM)-specific overexpression of GRK5 to recapitulate a selective aspect of hypertension and un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
51
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 57 publications
(55 citation statements)
references
References 44 publications
3
51
0
Order By: Relevance
“…Targeted overexpression of GRK2 to the vasculature is accompanied by increases in resting blood pressure and attenuated β-adrenergic signalling (Eckhart et al 2002). Similar results were obtained for the GRK5 isoform (Keys et al 2005). In addition to receptor desensitization, there is evidence that GRK2 is involved in the regulation of endothelial NO synthase (eNOS) activity, at least in hepatic portal endothelial cells (Fig.…”
Section: Genetic Variants Of G Protein-coupled Kinasesupporting
confidence: 59%
“…Targeted overexpression of GRK2 to the vasculature is accompanied by increases in resting blood pressure and attenuated β-adrenergic signalling (Eckhart et al 2002). Similar results were obtained for the GRK5 isoform (Keys et al 2005). In addition to receptor desensitization, there is evidence that GRK2 is involved in the regulation of endothelial NO synthase (eNOS) activity, at least in hepatic portal endothelial cells (Fig.…”
Section: Genetic Variants Of G Protein-coupled Kinasesupporting
confidence: 59%
“…5A) (25) under the control of the SMC-specific SM22␣ promoter (28,40,41). Immunoblots of aortic extracts demonstrated that the total level of USP20 in the USP20-Tg was 2 Ϯ 1-fold more than endogenous USP20 levels in non-Tg and that DN-USP20-Tg expression was about 3 Ϯ 1-fold greater than endogenous USP20 levels (Fig.…”
Section: Smc-specific Expression Of Usp20 and Dn-usp20 In Transgenicmentioning
confidence: 90%
“…The hypertension in male GRK5 transgenic mice is, in part, because of decreased ␤ 1 -adrenergic receptor activity, whereas the high blood pressure in female mice is because of increased activity of AT 1 Rs. 14 Dopamine D 2 R hypersensitivity occurs with disruption of the GRK6 gene in mice. 15 Therefore, abnormalities of GRK6 gene can lead to D 2 R supersensitivity, which can result in a decrease in norepinephrine release, leading to decreased blood pressure or, alternatively, causing an increase in D 2 R-mediated sodium transport in renal proximal tubules, leading to an increased blood pressure, instead.…”
Section: Gpcr Kinase Familymentioning
confidence: 99%